2010
DOI: 10.1111/j.1756-8765.2010.01110.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Control: Componential or Emergent?

Abstract: The past 25 years have witnessed an increasing awareness of the importance of cognitive control in the regulation of complex behavior. It now sits alongside attention, memory, language, and thinking as a distinct domain within cognitive psychology. At the same time it permeates each of these sibling domains. This introduction reviews recent work on cognitive control in an attempt to provide a context for the fundamental question addressed within this topic: Is cognitive control to be understood as resulting fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 54 publications
(85 reference statements)
1
40
0
2
Order By: Relevance
“…Although a previous study aiming to determine the organization and possible dissociability of the executive functions found them to be both diverse and unified (Miyake et al, 2000), it is only very recently has it been suggested that cognitive control is achieved via the interactions of control components (Badre, 2011). There is now emerging debate regarding whether cognitive control is better defined as comprising discrete functional components attributable to unique functional anatomy, whether it emerges from more basic psychological functions that often serve other purposes or whether it is best conceptualized as being both componential and emergent (Cooper, 2010; Juvina, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Although a previous study aiming to determine the organization and possible dissociability of the executive functions found them to be both diverse and unified (Miyake et al, 2000), it is only very recently has it been suggested that cognitive control is achieved via the interactions of control components (Badre, 2011). There is now emerging debate regarding whether cognitive control is better defined as comprising discrete functional components attributable to unique functional anatomy, whether it emerges from more basic psychological functions that often serve other purposes or whether it is best conceptualized as being both componential and emergent (Cooper, 2010; Juvina, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, consistent with the unity/diversity framework of executive functioning (Miyake et al, 2000), inhibition and updating processes would be conjointly involved in stimuli processing during the task. These two functions might be regulated by common core cognitive control processes (Cooper, 2010), namely WM mechanisms responsible for task context and goals maintenance (Braver et al, 2007). Classically, the interference effect in the task is characterized by slower reaction times (RTs) for RN than NN trials (D'Esposito et al, 1999;Jonides et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…While the range and number of executive functions that have been proposed suggests that significant progress has been made in understanding cognitive control, cataloguing and understanding the operation and interaction of executive control functions in specific tasks remains a significant challenge (Cooper, 2010). One of the more ambitious behavioural studies that has attempted to make progress on this issue is that of Miyake et al (2000), who were primarily concerned with the functions of response inhibition, set-shifting and memory updating / monitoring (i.e., "monitoring and coding incoming information for relevance to the task at hand and then appropriately revising the items held in working memory"; Miyake et al, 2000, p. 57).…”
mentioning
confidence: 99%